In Vitro and In Silico Wound-Healing Activity of Two Cationic Peptides Derived from Cecropin D in Galleria mellonella - Sandra Patricia Rivera-Sanchez; Iván Darío Ocampo-Ibáñez; Maria Camila Moncaleano; Yamil Liscano; Liliana Janeth Flórez Elvira; Yesid Armando Aristizabal Salazar; Luis Martínez-Martínez; Jose Oñate-Garzon (Antibiotics)
Background: Chronic wounds pose a significant public health challenge due to high treatment costs and the limited efficacy of current therapies. This study aims to evaluate the in vitro wound-healing activity and in silico interactions of two antimicrobial cationic peptides, derived from Galleria mellonella cecropin D, whose receptors are involved in tissue healing. Methods: Two peptides were tested: a long peptide (∆M2, 39 amino acids) and a short peptide (CAMP-CecD, 18 amino acids). Their cytotoxicity, as well as their effects on fibroblast proliferation and migration, were assessed using Detroit 551 cells. In parallel, molecular docking studies were conducted with AutoDock Vina to predict the binding affinities of these peptides to the key receptors involved in wound healing: the epidermal growth factor receptor (EGFR), the transforming growth factor beta receptor (TGFRβ2), and the vascular endothelial growth factor receptor (VEGFR). Results: In vitro assays showed that the short peptide exhibited lower cytotoxicity and significantly enhanced cell proliferation and migration, leading to a greater percentage of gap closure compared to the long peptide. A docking analysis revealed binding affinities of −6.7, −7.2, and −5.6 kcal/mol for VEGFR, EGFR, and TGFRβ2, respectively, with the RMSD values below 2 Å, indicating stable binding interactions. Conclusions: These findings suggest that the structure and cationic charge of the short peptide facilitate robust interactions with growth factor receptors, enhancing re-epithelialization and tissue regeneration. Consequently, this peptide is a promising candidate ligand for the treatment of chronic wounds and associated infections.